Existence of the Mild Solutions for Delay Fractional Integrodifferential Equations with Almost Sectorial Operators - Fang Li (Abstract and Applied Analysis)
This paper is concerned with the existence of mild solutions for the fractional integrodifferential equations with finite delay and almost sectorial operators in a separable Banach space X. We obtain existence theorem for mild solutions to the above-mentioned equations, by means of measure of noncompactness and the resolvent operators associated with almost sectorial operators. As an application, the existence of mild solutions for some integrodifferential equation is obtained.